1999
DOI: 10.1097/00005053-199910000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Patients' Perceptions of Facial Emotions in Depressed and Remitted States Are Associated with Relapse

Abstract: Within the framework of interpersonal and cognitive theories of depression, we investigated whether the perception of facial emotions was associated with subsequent relapse into depression. The 23 inpatients with major depression who remitted (65 admitted patients) were studied at admission (T0), at discharge (T1), and 6 months thereafter to assess relapse. They judged schematic faces with respect to the expression of positive and negative emotions. Six patients (26.1%) relapsed. High levels of perception of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
171
7
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(192 citation statements)
references
References 57 publications
11
171
7
3
Order By: Relevance
“…Indeed, an enhanced perception of happiness would be predicted to facilitate approach behaviour and social interaction. These changes may also be relevant to aspects of the action of SSRIs in patients with depression, who have been reported to show negative biases in the perception of social stimuli (eg Bouhuys et al, 1999). Citalopram administration also facilitated the recognition of fear from facial expression, which was contrary to our hypothesis of reduced identification of negative emotions following SSRI administration.…”
Section: Discussioncontrasting
confidence: 94%
“…Indeed, an enhanced perception of happiness would be predicted to facilitate approach behaviour and social interaction. These changes may also be relevant to aspects of the action of SSRIs in patients with depression, who have been reported to show negative biases in the perception of social stimuli (eg Bouhuys et al, 1999). Citalopram administration also facilitated the recognition of fear from facial expression, which was contrary to our hypothesis of reduced identification of negative emotions following SSRI administration.…”
Section: Discussioncontrasting
confidence: 94%
“…This is consistent with previous research that suggests depressed patients display negative biases in emotional processing [3 -6], including increased perception of ambiguous face emotions as negative [7,8]. The MDD group also displayed an overall non-valence-specific slowing of reaction times across all tasks at baseline, consistent with psychomotor slowing that is also observed in depression.…”
Section: (A) Emotional Processingsupporting
confidence: 90%
“…Indeed, depressed patients, as well as those at risk of depression [1,2], display negative biases in emotional processing across a range of cognitive domains, including perception, attention and memory [3][4][5][6]. For example, they display increased perception of ambiguous face emotions as negative [7,8], an attentional bias towards negative face emotions and self-referent words [9] and increased recall of negative versus positive self-referent words [10] compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Initial research began testing this question by presenting both unambiguous (clearly expressed negative or clearly expressed positive emotions) and ambiguous (mixed similar amount of expressed negative-positive emotions) schematic faces, and asking participants to rate how strongly each schematic depicted positive and/or negative emotions. Results showed that depression was associated with rating of mixed negative-positive schematic pictures as more negative (Bouhuys et al, 1999;Geerts & Bouhuys, 1998;Hale, 1998), and that such bias was associated with higher rumination levels (Raes, Hermans, & Williams, 2006) and predicted persistence of depression across time (Bouhuys et al, 1999;Geerts & Bouhuys, 1998).…”
Section: Introductionmentioning
confidence: 94%